A Study of Trends in Urdu Short Fiction - BiBi , Dr.Zeenat; Bibi, Dr. Raheela; Afridi, Dr. Muhammad Nasir; Gul, Misbah Noshaba; Fatima , Zeenat; Bacha , Jan; Uzma, (Al-Qanṭara, 2025)
Storytelling and a love for narratives are part of human nature. They have a deep connection with human psychology and natural instincts. This is why the Holy Qur’an has been described as Ahsan-ul-Qasas (the best of stories). Storytelling has long been used as a means to escape the bitterness of life and its hardships and to find emotional comfort. With this purpose in mind, the tradition of dastan (epic storytelling) emerged, and for a long time, humans adopted storytelling as a cultural practice. As time passed and human engagements became more complex, the novel emerged from the womb of the dastan in the form of realism. Gradually, people became inclined toward practical action and expressed dissatisfaction with supernatural elements. Rapid scientific progress further increased human preoccupations, and as a result, storytelling evolved into the modern short story. In today’s era, it has taken the form of micro-fiction. In Urdu literature, novel writing began after the War of Independence in 1857, as a result of social and cultural changes. Similarly, at the beginning of the twentieth century, the short story emerged to briefly portray the crisis-ridden life of Indian society. As far as fiction is concerned, both the novel and short story entered Urdu literature through English literary influence. Due to their narrative nature, they also drew inspiration from traditional dastans. Despite its relatively young age, the short story quickly reached the heights of popularity. It taught us to stay connected with literature despite our busy lives. In this way, the modern short story fulfilled the psychological needs of storytelling while continuing to evolve. In the historical background of the short story, Sajjad Haider Yildrim is regarded as the pioneer of romantic short fiction, while Premchand is considered the leader of progressive fiction. These two great writers opened two major chapters of romantic and progressive short story writing. As a result, many talented writers emerged and enriched Urdu literature with remarkable stories. These storytellers played a significant role in the evolution of the short story. During this period, rare and valuable stories were written that achieved the status of classic literature. Such stories are a precious intellectual and technical asset of Urdu literature, from which new writers continue to draw inspiration.